Особливості формування системи фінансових показників оцінювання кредитоспроможності позичальника – юридичної особи - Кіндрацька, Г. І.; Kindratska, G. I. (Видавництво Львівської політехніки, 2017)
У статті досліджено еволюцію підходів до механізму оцінювання кредитоспро- можності підприємств. Систематизовано основні переваги і недоліки сучасних методик визначення рівня кредитоспроможності позичальника-юридичної особи. Виокремлено проблеми аналізу його фінансового стану на етапі оцінювання кредитних можливостей згідно з вимогами нормативних документів, розроблених НБУ. Проведено порівняльний аналіз систем показників фінансового стану для великих і середніх підприємств. Запропоновано шляхи удосконалення механізму оцінювання кредитоспроможності позичальника-юридичної особи.

The evolution of evaluation mechanism creditworthiness of enterprises has been explored in the article. Critical analysis of recent National Bank’s of Ukraine regulatory documents, which regulate the procedure for determining the creditworthiness of the borrower – legal entity shows that they realize the different approaches and principles, but generally coordinate with best practice assessment of credit risk because too high requirements for borrowers may lead to their loss. Systematization of the main advantages and disadvantages of modern methods of determining the level of creditworthiness of the borrower – legal entity shows that the problem is mostly have based on the specific shortcomings of the legal framework. The comparative analysis of aggregate indicators of financial condition for large and medium-sized enterprises have showed that it does not fully meet of the system approach as suitable for tracking changes on certain indicators, rather than whole financial condition of the company. In particular, the unified approach drawing up a list of financial ratios ignores type of loan. If banks involve for evaluating the creditworthiness of the borrower – legal entity not only financial indicators recommended by the National Bank of Ukraine, but also subjective factors, it’s contributes to minimizing credit risk and to effectively stimulate enterprise business. Modern methodical approach to evaluating the creditworthiness of borrowers entities involves switching to transparent standards of work in which the decisive indicator of the probability is low creditworthiness of the borrower's financial position. We have suggested ways to improve the mechanism for creditworthiness evaluation of the borrower – legal entity
Formation features of the financial indicators system of creditworthiness evaluation of the borrower – legal entity
Keywords: системи показників фінансового стану; кредитоспроможність; financial indicators systems; creditworthiness; 657.6; 336.77